Lack of detectable fetal microchimerism in psoriasis vulgaris lesions and in non‐affected skin in spite of its presence in peripheral blood CD34‐positive and CD34‐negative cells. (13th August 2016) - Niepiekło‐Miniewska, W.; Baran, W.; Szepietowski, J.C.; Nowakowska, B.; Kuśnierczyk, P.
Abstract: Background: Microchimerism is defined as a stable presence of low numbers of cells derived from a different individual due to cell transfer between twins or between mother and fetus during pregnancy. Objective: Fetal cells in the organism of the mother (FMc) are postulated to play a role in autoimmune diseases. Psoriasis is a disease which has an autoimmune component, but no study on microchimerism in this disease has been reported. Methods: The easiest way to detect microchimerism is to look for male cells in blood or other tissues of a woman who previously delivered a son. Here, we looked for the presence of male cells in mononuclear cell subpopulations from peripheral blood and in skin samples of women with psoriasis and of healthy women. Results: We detected FMc in similar proportions of patients and controls in CD4+, CD8+ and CD34+ cells, whereas in CD34‐ cells they were present in higher fraction of controls, and similar but non‐significant difference was observed in CD19+ cells. No microchimeric cells were detected in patients' skin samples, both from affected and non‐affected skin, or in skin tissue from healthy control individuals. Conclusion: Our result does not prove the involvement of microchimerism in the aetiology of psoriasis.